2015
DOI: 10.1186/s10194-015-0533-5
|View full text |Cite
|
Sign up to set email alerts
|

Patients with migraine are right about their perception of temperature as a trigger: time series analysis of headache diary data

Abstract: BackgroundResearches to date on the association between headache and weather have yielded inconsistent results. Only a limited number of studies have examined the clinical significance of self-reported weather sensitivity. This study aimed to identify the difference in the association of headache with temperature between migraine patients with and without temperature sensitivity.Methods66 migraine patients (75.8 % female; mean age 43.3 ± 12.9 years) provided their 1-year headache diaries from 2007 to a headach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
4
21
0
1
Order By: Relevance
“…The contributions of individual trigger factors were similar, and the proportion of patients who reported any trigger(s) was higher in the SHD for 3 months. The frequent trigger factors in this analysis were in line with previous studies [ 2 , 3 , 10 , 29 30 ]. Several studies have suggested that stress is related to hormones, including cortisol and thyroid hormone, and may have a role in migraine pathogenesis [ 2 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…The contributions of individual trigger factors were similar, and the proportion of patients who reported any trigger(s) was higher in the SHD for 3 months. The frequent trigger factors in this analysis were in line with previous studies [ 2 , 3 , 10 , 29 30 ]. Several studies have suggested that stress is related to hormones, including cortisol and thyroid hormone, and may have a role in migraine pathogenesis [ 2 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…It is unclear what portion of these headaches were thunderclap‐like, but these meteorological parameters were quite different from those associated with RCVS onset in our study. One study conducted in Taiwan showed that there were higher migraine attack incidence rates when the weather was cool, conditions more similar to those we found to be associated with RCVS occurrence.…”
Section: Discussionsupporting
confidence: 85%
“…The majority of Google users live in the northern hemisphere; thus, seasonal variations in the time series mainly reflected this population. The peaks of interest in pain-related topics reflected previously reported relationships of pain location and the season for Headaches [51], viral infection of the upper airways (Ear pain, Sore throat), heartburn [52] or angina pectoris (Chest pain) [53], Abdominal pain [54,55], Low back pain [56], sexual activity (Dyspareunia) [57], and injuries (limb pain) [58]. Interestingly, the lowest RSVs for most of the topics were observed in December, which may be associated with the seasonal holidays, when people's attention could be away from the Internet.…”
Section: Time Coursesupporting
confidence: 59%